-60=6(x-9)

Simple and best practice solution for -60=6(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -60=6(x-9) equation:



-60=6(x-9)
We move all terms to the left:
-60-(6(x-9))=0
We calculate terms in parentheses: -(6(x-9)), so:
6(x-9)
We multiply parentheses
6x-54
Back to the equation:
-(6x-54)
We get rid of parentheses
-6x+54-60=0
We add all the numbers together, and all the variables
-6x-6=0
We move all terms containing x to the left, all other terms to the right
-6x=6
x=6/-6
x=-1

See similar equations:

| 8x^2-11x=76 | | 2y+8=6y-12 | | 2x-3(4x+5)=-2-8(x+7) | | 1/3(x-1)=3/4x+1/6 | | 6x-36=4x | | 30+6w=12w | | 2r+15=37 | | 9(q-4=)-8 | | n/9-9=2 | | 9(q-4=-8 | | 234=27c | | x/6+17=31 | | -3j+-1=5 | | 16=4+3b | | 55-5n=20 | | -4(5x+2)+2x+4=50 | | 13=-7-2n | | 4(x+8)+8x=10 | | 11x-7=4x+8 | | x/2+9=39 | | 3x+18=9x+38 | | 24x=18x | | 3b+6=-11 | | 4y=y=75 | | 33h=240 | | 5^6x+5/125^3x−1=5^−5x+2 | | Y=3b+6 | | 3x+20=33 | | 39=9-6v | | f*7=84 | | 56x+5/1253x−1=5−5x+2 | | 7m-(-7)=56 |

Equations solver categories